Sezonowa dynamika saproksylicznych chrząszczy (Coleoptera) występujących w próchnie brzóz (Betula spp.) w Kampinoskim Parku Narodowym - Sawoniewicz, Michał (Leśne Prace Badawcze, 2015)
The aim of the study was to identify the seasonal changes in the number of saproxylic beetles connected with birch in the Kampinos National Park. The research was conducted for 12 consecutive months in research areas representing 10 different site types. The beetles were collected from wood using photoeclectors. The largest number of species was collected in April and the lowest in January. An increase in number occurred during spring and summer months for species associated only with rotting wood, fructifications of tree fungi, the subcortical environment and hollows. In the same period the number of species not associated or potentially associated with decaying trees and wood decreased. During winter months, the differences in the number of trapped specimens were the smallest. The proportion of zoophagous species amongst the collected specimen increased in autumn and winter. The share of saprophagous species was the highest during the summer-autumn period and the share of mycetophages (jointly with myxomycophages) was the highest during spring and summer. We distinguished two separate groups of Coleoptera with the first one (ʻsummer groupʼ) including species trapped during late-spring and summer months, while the second one (ʻwinter groupʼ) includes species found in autumn, winter and early-spring months. In the ʻsummer groupʼ, an average of 55.8 species was trapped each month with 331.2 specimen of Coleoptera, while in the ʻwinter groupʼ an average of 56.1 species with 228.4 Coleoptera specimen were caught.